Governança financeira internacional: atores, instituições e dimensões contemporâneas - Mazzola, Camila Suveges Cerchiari (2023)
The present work proposes to present a study on international financial governance in the recent landmarks of the discussion on global governance. The time frame takes place after the 2007/08 crisis and the analysis of the actors and institutions that make up the theme is a key point for understanding the evolutions and challenges faced in the contemporary context. The problem that directs this research is part of the debates about the role of international organizations in the framework of global economic dynamics